HREATS OF ECONOMIC SECURITY OF INDUSTRIAL ORGANIZATIONS WHILE PROVIDING EQUIPMENT IN THE CONDITIONS OF IMPORT SUBSTITUTION - A. Savin (Publishing House of the State University of Management, 2017)
Annotation The article examines the consequences of implementing the policy of import substitution in providing technological equipment for the Russian extractive industry sector. An illustrative example of a corporate confrontation between JSC «Kopeysk Machine-Building Plant» and PJSC «Uralkali», generated by a galloping increase in the prices of supplied mining equipment and unsatisfactory conditions for its maintenance, is given. The conclusion is made about mutual threats to the economic security of cooperating industrial organizations of the situation of artificial restriction of competition between equipment manufacturers.